Pediatric Hearing Aid Management: Parent-Reported Needs for Learning Support. Issue 6 (November 2016) - Muñoz, Karen; Rusk, Stephanie E. P.; Nelson, Lauri; Preston, Elizabeth; White, Karl R.; Barrett, Tyson S.; Twohig, Michael P.
Abstract : Objectives: The aim of this study was to investigate parent learning and support needs related to hearing aid management for young children, and factors that influence parent-reported hours of hearing aid use. Design: A cross-sectional survey design was used to collect survey data in seven states. The child's primary caregiver completed a demographic form, a questionnaire to explore parent learning and support needs as well as their challenges with hearing aid use, and the patient health questionnaire to identify symptoms of depression. Three hundred and eighteen parents completed the questionnaires. Results: Responses were analyzed for 318 parents of children (M = 23.15 months; SD = 10.43; range: 3 to 51) who had been wearing hearing aids (M = 15.52; SD = 10.11; range: <1 to 50 months). Even though the majority of parents reported receiving the educational support queried, approximately one-third wanted more information on a variety of topics such as loaner hearing aids, what their child can/cannot hear, financial assistance, how to meet other parents, how to do basic hearing aid maintenance, and how to keep the hearing aids on their child. The most frequently reported challenges that interfered with hearing aid use (rated often or always) were child activities, child not wanting to wear the hearing aids, and fear of losing or damaging the hearing aids. Forty-two percent of parents reported that, on good days, their child used hearing aids all waking hours. Multiple regression was used to compare the effect on parent-reported typical hours of hearing aid use based on good days for the variables of (1) presence of depressive symptoms for the parent, (2) child age, (3) family income, (4) primary caregiver education level, (5) presence of additional disabilities for the child, (6) degree of hearing loss, and (7) length of time since the child was fitted with hearing aids. There were statistically significantly fewer hours of reported hearing aid use when parents reported mild to severe symptoms of depression, lower income, less education level, and when children had mild hearing loss or additional disabilities. Conclusion: Although parents reported overall that their needs for hearing aid education and support had generally been met, there were important suggestions for how audiologists and other service providers could better meet parent needs. Hearing aid use for young children was variable and influenced by a variety of factors. Understanding parent experiences and challenges can help audiologists more effectively focus support. Audiologists are more likely to meet the needs of families if they take care to provide access to thorough and comprehensive education and ongoing support that is tailored to address the unique needs of individual families. Abstract : Supplemental Digital Content is available in the text.